THU0376 Serum leptin, resistin, visfatin and adiponectin levels in tumor necrosis factor receptor-associated periodic syndrome (TRAPS). (23rd January 2014) - Cantarini, L.; Obici, L.; Simonini, G.; Cimaz, R.; Bacarelli, M.R.; Merlini, G.; Vitale, A.; Lucherini, O.M.; Brizi, M.G.; Galeazzi, M.; Fioravanti, A.
Abstract : Background: White adipose tissue produces more than 50 adipokines and other molecules that participate through endocrine, paracrine, autocrine or juxtacrine mechanisms of action in a wide variety of physiopathological processes, including food intake, insulin sensitivity, vascular sclerotic processes, immunity and inflammation (1, 2). Tumor necrosis factor (TNF) receptor-associated periodic syndrome (TRAPS) is the most common autosomal dominant autoinflammatory disorder and is caused by mutations in the TNFRSF1A gene encoding the 55-kD receptor for TNF-α (TNFRSF1A) (3). Objectives: the aims of our study were to evaluate serum leptin, resistin, visfatin and adiponectin levels in patients with tumor necrosis factor receptor-associated periodic syndrome (TRAPS), in comparison to healthy controls, and to correlate their levels to parameters of disease activity and/or severity. Methods: serum leptin, resistin, visfatin and adiponectin levels were obtained from 14 TRAPS patients carrying mutations involving cysteine residues, from 16 TRAPS patients carrying other mutations, and from 16 healthy controls. Demographic, clinical and laboratory parameters, including amyloidosis were entered for each patient. Comparisons between groups as well as reciprocal comparisons have been evaluated. Results: Serum leptin, resistin, visfatin and adiponectin did not significantly differ among the 3 groups. Serum leptin significantly correlated with the number of attacks/year (multiple R=0.32, multiple adjusted R 2 =0.19, p<0.03). Serum adiponectin levels significantly correlated with the presence of amyloidosis (multiple R=0.79, multiple adjusted R 2 =0.57, p<0.03). Adiponectin values were a significant predictor for amyloidosis (AUC 0.75, 95 CI: 0.56-0.94, p<0.03), with a predicting cut-off value set at 23.16 pg/ml, the predictive positive value was 53.8%. Visfatin serum levels resulted respectively related to leptin (rs =0.42, r 2 =0.18, p<0.02) and to resistin (rs =0.57, r 2 =0.32, p<0.01) serum levels; whilst leptin and resistin serum levels did not reciprocally correlate. Conclusions: Although a prospective design study and larger cohort are mandatory, adipokines serum levels and their correlations with parameters of disease activity and/or severity, seem to show a baseline pattern in TRAPS patients. References: Lago F, Dieguez C, Gόmez-Reino J, Gualillo O. Adipokines as emerging mediators of immune response and inflammation. Nat Clin Pract Rheumatol 2007;3:716-24. Cantarini L, Simonini G, Fioravanti A, et al.Circulating levels of the adipokines vaspin and omentin in patients with juvenile idiopathic arthritis, and relation to disease activity. Clin Exp Rheumatol 2011 [Epub ahead of print]. McDermott MF, Aksentijevich I, Galon J, et al. Germline mutations in the extracellular domains of the 55 kDa TNF receptor, TNFR1, define a family of dominantly inherited autoinflammatory syndromes. Cell 1999; 97:133-44. Disclosure of Interest: None Declared